Revitalizing Worship In The Post-Pandemic Church: Towards A Liturgy Of Thanksgiving - Hengki Bonifacius Tompo; David Kristanto; Adri Prematura Wicaksono (Manna Rafflesia, 2022)
Theological discussions related to the post-pandemic condition of the church have attracted significant attention. Generally speaking, those discussions focus on the mode of worship in the future: whether to remain online, back offline or adopt the hybrid mode of worship. In this article, the authors argue that the mode of worship in the post-pandemic condition should not be seen as operative per se, but it should be based on a deep reflection of the church on what is the essence of worship and how could the church reflect it to the congregations in the church and the world outside the church. To reflect the Gospel appropriately, the church should seek to revitalize worship in the post-pandemic condition. This article suggests that such a revitalization could be achieved through constructing a thanksgiving liturgy. The post-pandemic condition could be seen as a suitable opportunity for the church to reflect its joy and gratitude for the grace of God that renews and heals the creation.